2021
DOI: 10.1097/md.0000000000027444
|View full text |Cite
|
Sign up to set email alerts
|

Low-field thoracic magnetic stimulation increases peripheral oxygen saturation levels in coronavirus disease (COVID-19) patients

Abstract: Severe acute respiratory syndrome coronavirus-2 may cause low oxygen saturation (SpO 2 ) and respiratory failure in patients with coronavirus disease (COVID-19). Hence, increased SpO 2 levels in COVID-19 patients could be crucial for their quality of life and recovery. This study aimed to demonstrate that a 30-minute single session of dorsal low-field thoracic magnetic stimulation (LF-ThMS) can be employed to increase SpO 2 levels in COVID-19… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 45 publications
(81 reference statements)
0
1
0
Order By: Relevance
“…ELF-MFs include stimulation in the range of 0-300 Hz frequency and have biological effects on tissues. There are data showing that ELF-MFs cause functional changes in muscle, neural tissues and bones [12,13]; some researchers even claim that ELF-MFs may impair the ability of the SARS-CoV-2 virus to replicate and attack host cells [14]. It is indicated that ELF-MFs have a beneficial impact on brain tissue and its functions [15][16][17], suggesting that this stimulation method could be advantageous for patients after a stroke.…”
Section: Introductionmentioning
confidence: 99%
“…ELF-MFs include stimulation in the range of 0-300 Hz frequency and have biological effects on tissues. There are data showing that ELF-MFs cause functional changes in muscle, neural tissues and bones [12,13]; some researchers even claim that ELF-MFs may impair the ability of the SARS-CoV-2 virus to replicate and attack host cells [14]. It is indicated that ELF-MFs have a beneficial impact on brain tissue and its functions [15][16][17], suggesting that this stimulation method could be advantageous for patients after a stroke.…”
Section: Introductionmentioning
confidence: 99%